A review on Chemistry and Therapeutic effect of Pyrazole: Exploring the Role of Medicinal Chemistry in Drug Discovery and Development (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Medicinal ChemistryDevelops the new synthetic drug molecules or series has shown results inmany other disciplines or branches of science are such as biochemistry, combinatorial chemistry,,photochemistry, pharmacology, medicinal chemistry. Focus on various studies medicinal chemists arealso trying to develop new chemical active molecules or lead molecules against disease ordisordermedicinal chemistry play an important role to drug discovery and development. Develops the newsynthetic drug molecules or series has shown results in many other disciplines or branches of science aresuch as biochemistry, combinatorial chemistry,, photochemistry, pharmacology, medicinal chemistry.